PENGARUH SPIRITUAL QUOTIENT TERHADAP KATANGGUHAN MASYARAKAT SEKOLAH - Muhasim Muhasim; Zulfikar Muhammad (LP2M Universitas Ibrahimy, 2021)
Disasters are cannot be separated from our daily lives. The threat of disaster at any time lurks the Indonesian nation. Therefore, Indonesian people must be ready and resilient in facing disasters so that they can minimize fatalities. Various things are done, all components are expected to work together to achieve a disaster resilient society. BNPB (The National Disaster Mitigation Agency) creates various programs for disaster preparedness to minimize fatalities. Spiritual Quotien (spiritual intelligence) as an element in religion which has a strategic role in disaster preparedness. The purpose of this study was to determine the effect of spiritual quotient level on society resilience in the school environment. This research method uses a correlational cross-sectional approach which measuring the variables at one particular moment. The population in this study was SMA Muhammadiyah I Kota Malang. The sample used was 75 people. The sampling technique used purposive sampling. The group will take measurements related to the level of spiritual quotient and society resilience. Furthermore, data analysis will be carried out to see the effect of the spiritual quotient level on society resilience based on the significance with a different test analysis using the Wilcoxon statistical test with a significance level of 95%. The results showed a significant value of 0.004 which means that there is a significant effect of spiritual quotient on society resilience at SMA Muhammadiyah 1 Kota Malang. This research is expected to provide input on the importance of a spiritual quotient in increasing the resilience of school societies in disaster-prone area.